2009
DOI: 10.1111/j.1551-2916.2009.02976.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Phase Stability Studies in Spray Deposited KNO3:PVA Composite Films

Abstract: The composite films of potassium nitrate (KNO 3 ):poly(vinyl alcohol) (PVA) have been prepared at different temperatures by spray-deposition technique. Ferroelectric hysteresis loops were traced at room temperature for the composite films using modified Sawyer and Tower circuit. The X-ray diffraction studies confirm the existence of ferroelectric phase III of KNO 3 in the composite films at the room temperature, where this phase in pure KNO 3 films is known to exist in the temperature range 1101-1241C. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The image of the composite film containing 50 wt.% of Kno 3 show the uniform distribution of Kno 3 in PVa matrix and grain size of ~225 nm. Earlier studies using atomic force microscopy (aFM) technique also revealed grain size of similar order in these films having this composition [52]. However, the clustering of the Kno 3 particles has been observed in the composite films above 50 wt.% composition of Kno 3 .…”
Section: Resultsmentioning
confidence: 91%
“…The image of the composite film containing 50 wt.% of Kno 3 show the uniform distribution of Kno 3 in PVa matrix and grain size of ~225 nm. Earlier studies using atomic force microscopy (aFM) technique also revealed grain size of similar order in these films having this composition [52]. However, the clustering of the Kno 3 particles has been observed in the composite films above 50 wt.% composition of Kno 3 .…”
Section: Resultsmentioning
confidence: 91%
“…In this region t < t s, the finite grain size effect on the switching current is negligible since the size of domain is much less than the grain size. Therefore, the theoretical fit to switching current in the region t ≥ t s was obtained using equation (2), which takes into account the effect of grain size. Hence the switching time t s is the time at which the switching kinetics changes from independent of grain size to grain size limitations.…”
Section: Resultsmentioning
confidence: 99%
“…The polarization reversal takes place by applying an external electric field greater than its coercive field and this property can be utilized for the memory devices application [1,2]. Thus, the study of switching transients in the composite films can be useful in understanding the switching mechanism as well as to find its potential applications in memory devices.…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that 180 domain switching is easier than the 90 domain switching. 17 34 35 Moreover, the orientation of 90 is directly related to the back switching phenomenon. The least percentage of back switching suggests that the interaction between the domains and structural defects is significantly reduced in the composite films which could be responsible for larger P r and smaller coercive field, E c in composite films.…”
Section: Hysteresis Loop Measurementsmentioning
confidence: 99%
“…The back switching percentage was calculated from the hysteresis loop characteristics. 17 34 35 Back switching (%age) was calculated in the composite films of NKN:PVA (1:1) deposited at 130, 150, 170, 200 and 250 C and found to be 20. 26, 19.56, 14.78, 21.29 and 23.23% respectively.…”
Section: Hysteresis Loop Measurementsmentioning
confidence: 99%